Characterization of Thin Alluvial Bed Aquifers in Manggar River Balikpapan East Kalimantan Indonesia - Totok Sulistyo; Ali Abrar (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2017)
AbstractManggar Village is suburban, located in District of East Balikpapan, East Borneo Indonesia. In dry season, clean water crisis always hit this area. Therefore in order to full fill the need of water for domestic use the inhabitant of this area use dug well water. Dug well water comes from the upper most ground water that is stored and transmitted by relatively thin layer of alluvium deposit. In this research surface elevation measurement was done to control the elevation of dug well so that the depth of dynamic water level (DWL) could be determined accurately. The equipotential map was made based on the DWL, then flow line can be drawn and gradient hydraulics (i) can be calculated. Coefficient of permeability (k) that were resulted from fall head test has shown value 1.284 x 10-3 up to 11.45 x 10-3 cm/sec which gradually increases toward beach. According to the results of serial test and calculation the ground water transmissibility and velocity increases toward the beach. Generally groundwater has high hardness. The groundwater close to the beach has been mixed with sea water.